The formation of tretinoin-PEG 6000 solid-solid solution to increase the dissolution rate of tretinoin - Christina Avanti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
The formation of solid-solid dispersion of tretinoin which is insoluble in water into water soluble carrier PEG, might accelerate solubility and dissolution rate. The objectives of this study were to obtain dissolution profile and physical properties of Tretinoin-PEG solid dispersion which was prepared by solventfusion method, to obtain the composition of Tretinoin and PEG in which produce solid dispersion with optimum dissolution rate and to obtain the composition of Tretinoin-PEG, which produce an interstitial solid-solid solution. Solvent fusion method at low temperature was choosen to prepare the solid dispersion system. The physical state of formed solid dispersion was determined by X-Ray diffractometer. To unveil the information about the solubility and dissolution rate of tretinoin, a test toward the dissolution rate of tretinoin was performed into the dissolution medium phosphate buffer. The X-Ray diffractogram of tretinoin-PEG solid dispersion in all composition indicated that tretinoin hasformed a molecular dispersion in the PEG crystals in all composition. In solid dispersion was obtained by solvent-fusion method in molecular or in solid-solid solution. Dissolution efficiency (DE) value prooved that molecular dispersion of tretinoin-PEG could increase the dissolution rate of tretinoin. Thus it could concluded that in comparison to the tretinoin and its physical mixture, the solid dispersion of tretinoin-PEG led the higher dissolution rate and the optimum rate was achieved by composition of 1=100 with DE value = 74.Key words : Tretinoin, PEG, Solid Dispersion, Dissolution Rate